On the initial shear field of the cosmic web - Rossi, Graziano (Monthly notices of the Royal Astronomical Society, 2012)
The initial shear field, characterized by a primordial perturbation potential, plays a crucial role in the formation of large-scale structures. Hence, considerable analytic work has been based on the joint distribution of its eigenvalues, associated with Gaussian statistics. In addition, directly related morphological quantities such as ellipticity or prolateness are essential tools in understanding the formation and structural properties of haloes, voids, sheets and filaments, their relation with the local environment, and the geometrical and dynamical classification of the cosmic web. To date, most analytic work has been focused on Doroshkevich's unconditional formulae for the eigenvalues of the linear tidal field, which neglect the fact that haloes (voids) may correspond to maxima (minima) of the density field. I present here new formulae for the constrained eigenvalues of the initial shear field associated with Gaussian statistics, which include the fact that those eigenvalues are related to regions where the source of the displacement is positive (negative): this is achieved by requiring the Hessian matrix of the displacement field to be positive (negative) definite. The new conditional formulae naturally reduce to Doroshkevich's unconditional relations, in the limit of no correlation between the potential and the density fields. As a direct application, I derive the individual conditional distributions of eigenvalues and point out the connection with previous literature. Finally, I outline other possible theoretically or observationally oriented uses, ranging from studies of halo and void triaxial formation, development of structure-finding algorithms for the morphology and topology of the cosmic web, to an accurate mapping of the gravitational potential environment of galaxies from current and future generation galaxy redshift surveys.